2006
DOI: 10.3766/jaaa.17.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Clinical Trial: Tinnitus Masking versus Tinnitus Retraining Therapy

Abstract: A controlled clinical study was conducted to evaluate prospectively the clinical efficacy of tinnitus masking (TM) and tinnitus retraining therapy (TRT) in military veterans having clinically significant tinnitus. Qualifying patients were placed into the two groups in an alternating manner (to avoid selection bias), and treatment was administered at 0, 3, 6, 12, and 18 months. Outcomes of treatment were evaluated using three self-administered tinnitus questionnaires (Tinnitus Handicap Inventory, Tinnitus Handi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 22 publications
4
95
2
2
Order By: Relevance
“…47 We identifi ed one trial in this review, and that work suggested that TRT is more eff ective than masking. 48 A subsequent trial used TRT as a control for acceptance and commitment therapy, 49 which has developed from CBT. TRT had a small benefi t in that study.…”
Section: Standard Treatmentsmentioning
confidence: 99%
“…47 We identifi ed one trial in this review, and that work suggested that TRT is more eff ective than masking. 48 A subsequent trial used TRT as a control for acceptance and commitment therapy, 49 which has developed from CBT. TRT had a small benefi t in that study.…”
Section: Standard Treatmentsmentioning
confidence: 99%
“…TRQ scores of the Neuromonics group was significantly better than the scores of the Noise + counselling group (p = 0.008) and Counselling only group (p = 0.014). VAS also showed Henry et al 30 studied 123 patients to evaluate the clinical efficacy of tinnitus masking (TM) and tinnitus retraining therapy (TRT) methods. Patients were placed quasi-randomly (alternating placement) into TM group (59, M = 53, F = 6) or TRT group (64 all males).…”
Section: Tinnitus Matching and Masking For Tinnitus Therapymentioning
confidence: 99%
“…Jastreboff 56 stressed on the effectiveness of sound therapy in tinnitus intervention, and also on the importance of hearing aids in providing sound therapy. Henry et al 30 focused on the assessment guidelines and the use of Audiologic Tinnitus Management by audiologist in the clinical management of tinnitus.…”
Section: Review Studiesmentioning
confidence: 99%
“…1) Band noise stimulus: Band noise stimulus is used in TM approach [2]. In this approach the desired noise is a band of noise with a frequency emphasis that approximates the frequency of perceived tinnitus.…”
Section: B Inhibition Of Oscillation By External Noise Stimulusmentioning
confidence: 99%
“…A mechanism of tinnitus generation has been hypothesized from the viewpoint of general neurophysiology [1]. There are two typical sound therapy techniques where those who suffer from tinnitus hear these therapeutic sounds for several hours a day [2]: TM (Tinnitus Masking) technique and TRT (Tinnitus Retraining Therapy). Band noise and white noise are actually provided to the sufferers from tinnitus as therapeutic sound in TM and TRT, respectively.…”
Section: Introductionmentioning
confidence: 99%